Differential Neural Responses Underlying the Inhibition of the Startle Response by Pre-Pulses or Gaps in Mice - Moreno-Paublete, Rocio; Canlon, Barbara; Cederroth, Christopher R. (Frontiers in Cellular Neuroscience, 2017)
Gap pre-pulse inhibition of the acoustic startle (GPIAS) is a behavioral paradigm used for inferring the presence of tinnitus in animal models as well as humans. In contrast to pre-pulse inhibition (PPI), the neural circuitry controlling GPIAS is poorly understood. To increase our knowledge on GPIAS, a comparative study with PPI was performed in mice combining these behavioral tests and c-Fos activity mapping in brain areas involved in the inhibition of the acoustic startle reflex (ASR). Both pre-pulses and gaps efficiently inhibited the ASR and abolished the induction of c-Fos in the pontine reticular nucleus (PnC). Differential c-Fos activation was found between PPI and GPIAS in the forebrain whereby PPI activated the lateral globus pallidus (LGP) and GPIAS activated the primary auditory cortex. Thus, different neural maps are regulating the inhibition of the startle response by pre-pulses or gaps. To further investigate this differential response to PPI and GPIAS, we pharmacologically disrupted PPI and GPIAS with D-amphetamine or Dizocilpine (MK-801) to target dopamine efflux and to block NMDA receptors, respectively. Both D-amp and MK-801 efficiently decreased PPI and GPIAS. We administered Baclofen, an agonist GABAB receptor, but failed to detect any robust rescue of the effects of D-amp and MK-801 suggesting that PPI and GPIAS are GABAB-independent. These novel findings demonstrate that the inhibition of the ASR by pre-pulses or gaps is orchestrated by different neural pathways.